(untitled)
o"kZ 2010 esa ekulwuksRrj _rq ds nkSjku nks pØokrh; rwQku fufeZr gq, FksA tSls ‘fxjh’ uked vfr izpaM pØokrh; rwQku ¼oh-,l-lh-,l-½ 19 vDrwcj dks fufeZr gqvk vkSj ;g 22 rkjh[k dks E;kaekj leqnz rV dks ikj dj x;k vkSj nwljk ‘tky’ uked izpaM pØokrh; rwQku ¼,l-lh-,l-½ 2 uoacj dks fufeZr gqvk vkSj ;g psUuS ds mRrjh Hkkx ds lehi mRrjh rfeyukMq & nfk.kh vka/kz izns’k ds leqnzh rVksa dks 07 uoacj dks ikj dj x;k ftldh otg ls rfeyukMq vkSj nfk.kh vka/kz izns’k ds leqnz rVh; ks=ksa esa u dsoy rhoz iou ls cfYd mlls gqbZ Hkkjh o"kkZ ls Hkkjh kfr gqbZA okLrfod le; foLr`r ks= iwokZuqeku xR;kRed fHkUurkvksa ds lkIrkfgd vkSlr ds vk/kkj ij nks lIrkg ds fy, rS;kj fd, x, gSa tks- bZ- lh- ,e- MCY;w- ,Q-] ,u- bZ- lh- ih- rFkk nksuksa ds 2 ekWMYl vkSlr ¼2 ,e- ,- oh- bZ-½ ds ;qfXer ekWMy ifj.kke ij vk/kkfjr gSaA lkIrkfgd vkSlr] iou vkSj lkisfkd Hkzfeyrk ds 5&11 fnuksa ds izpkyukRed iwokZuqeku 14 vDrwcj 2010 ds vkjafHkd fLFkfr ij vk/kkfjr gSa ftlls irk pyk gS fd 18&24 vDrwcj dh vof/k ds nkSjku e/; caxky dh [kkM+h ds Åij fuEu nkc dk pØokrh; ldqZys’ku Fkk tks vfr izpaM pØokrh; rwQku ‘fxjh’ ds leku FkkA ‘tky’ uked pØokr dh mRifRr dk 2 ,e- ,- oh- bZ- esa vPNh rjg irk yxk fy;k x;k FkkA bldk iwokZuqeku 12&18 fnuksa ds fy, oS/k Fkk vkSj ;g 21 vDrwcj 2010 dh vkjafHkd fLFkfr ij vk/kkfjr FkkA 2 ,e- ,- oh- bZ- iwokZuqeku 1&7 uoacj rd ds fy, oS/k Fkk tks 28 ,oa 21 vDrwcj dh vkjafHkd fLFkfr;ksa ij vk/kkfjr Fkk ¼buds iwokZuqeku dh vof/k Øe’k% 5&11 fnuksa rFkk 12&18 fnuksa dh Fkh½ ftlesa Li"V :i ls n’kkZ;k x;k gS fd rfeyukMq leqnz rV vkSj blls yxs gq, vka/kz izns’k ds ks= esa izsfkr dh xbZ folaxfr;ksa ls dkQh vf/kd ?kukRed o"kkZ folaxfr;k¡ ns[kh xbZ gSaA bl izkjafHkd v/;;u esa vkxs crk;k x;k gS fd lkIrkfgd pØokrh; Hkzfeyrk ds ekWMy iwokZuqekuksa dh vf/kdre folaxfr =qfV yxHkx &0-8 ls &1-0 × 10&5 izfr lSds.M dks fuEu LRkjh; vf“lj.k folaxfr yxHkx &0-8 ls &1-0 × 10&5 izfr lSds.M ds lkFk feyus ij m".kdfVca/kh pØokr cuus dh laHkkouk curh gSA rFkkfi bl flLVe ds pØokr ds :i esa rhozhdj.k gsrq Fkzs’kgksYM oSY;w dh igpku djus ds fy, vkSj vf/kd ekeyksa ds fo’ys"k.k djus dh vko’;drk gSA There were two cyclonic storms formed during the post monsoon season of 2010 viz., “Giri” a very severe cyclonic storm (VSCS) formed on 19th October and crossed the Myanmar coast on 22nd and the second system “Jal” a severe cyclonic storm (SCS) formed on 2nd November and crossed north Tamil Nadu-south Andhra Pradesh coasts, close to north of Chennai on 7th November, which caused lot of damage in Tamil Nadu and south Andhra Pradesh coast associated with not only strong wind but also due to associated heavy rainfall. The real time extended range forecasts in terms of weekly mean of dynamical variables are prepared for two weeks based on the coupled model outputs from ECMWF, NECP and the 2 models average (2MAVE) of both. The operational forecast for days 5-11 of weekly mean wind and relative vorticity based on 14th October, 2010 initial condition indicates cyclonic circulation at low level over the central Bay of Bengal during the period from 18-24 October associated with the very severe cyclone “Giri”. The genesis of the cyclone “Jal” was very much captured in the 2MAVE forecast valid for 12-18 days forecast based on the initial condition of 21st October, 2010. The 2MAVE forecast valid for 1-7 November based on 28 October and 21 October initial conditions (with forecast period of days 5-11 and days 12-18 respectively) also clearly indicated large positive rainfall anomalies over Tamil Nadu coast and adjoining coastal Andhra Pradesh region like that of observed rainfall anomalies. This preliminary study further indicates that the model forecasts anomaly of weekly cyclonic vorticity maximum of about 2.5´10-5 sec-1 combined with a low level convergence anomaly of about -0.8 to -1.0 ´ 10-5 sec-1 may lead to formation of a tropical cyclone. However, more number of cases required to be analysed for the proper identification of the threshold values for intensification of the system into a cyclone. , number=1, journal=MAUSAM, year=2013, month=Jan., pages=171–188